1999
DOI: 10.1159/000040952
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival in Primary Plasma Cell Leukemia after Therapy with VAD, Autologous Blood Stem Cell Transplantation and Interferon-Alpha

Abstract: Primary plasma cell leukemia (PCL) is a rare form of plasma cell neoplasm with a poor prognosis. Conventional melphalan-based treatments have been most disappointing. We report the case of a 62-year-old man with a primary form of PCL treated with VAD combination achieving an objective response, and who received high-dose melphalan and autologous peripheral blood stem cell (PBSC) transplantation followed by interferon-α. During the remission time, lasting for 3 years, an infiltration by large granular lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Intensification of therapy using high dose melphalan was reported in PCL around the same time as application of this regime in multiple myeloma. 11 There have been several case reports [12][13][14][15][16][17] as well as descriptions of one 2 and five 1 patients in two previously reported series of patients with PCL describing the value of melphalan or other high-dose therapy when combined with autologous transplantation. In general, patients received induction with aggressive combination chemotherapy and the median survival after autografting ranged from 3 to 59 months.…”
Section: Discussionmentioning
confidence: 99%
“…Intensification of therapy using high dose melphalan was reported in PCL around the same time as application of this regime in multiple myeloma. 11 There have been several case reports [12][13][14][15][16][17] as well as descriptions of one 2 and five 1 patients in two previously reported series of patients with PCL describing the value of melphalan or other high-dose therapy when combined with autologous transplantation. In general, patients received induction with aggressive combination chemotherapy and the median survival after autografting ranged from 3 to 59 months.…”
Section: Discussionmentioning
confidence: 99%
“…Kürzlich wurde über die erfolgreiche Behandlung mit Fludarabin berichtet [9]. In anderen Fallbeschreibungen wurden intensivierte Therapie-Programme wie Hochdosis-Cyclophosphamid mit Etoposid oder Hochdosis-Melphalan [10] in Kombination mit peripherer Stammzell-Transplantation erfolgreich eingesetzt. Wir behandelten zwei Patienten mit primärer Plasmazell-Leukämie erfolgreich nach dem BMF-Protokoll für B-Zell Leukämien.…”
Section: Therapieunclassified
“…A literature review showed only one case of plasma cell leukaemia with extended survival after autologous bone marrow transplantation (Kun‐Huei Yeh et al. , 1995) and a few other cases with variable results (Sajeva et al ., 1996; Majolino et al ., 1998; Sion et al ., 1998; Leleu et al ., 1999; Panizo et al ., 1999). In one report (Koskela et al ., 1998), a patient with multiple myeloma developed plasma cell leukaemia only 3 months after autologous PBSCT.…”
Section: Discussionmentioning
confidence: 99%